2006
DOI: 10.1111/j.1365-2672.2006.03170.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of flow cytometry for the determination of minimal inhibitory concentration of several antibacterial agents on Mycoplasma hyopneumoniae

Abstract: Aim:  In this study, flow cytometry was evaluated for the determination of the minimal inhibitory concentrations (MICs) of nine antibacterial agents (enrofloxacin, ciprofloxacin, oxytetracycline, chloramphenicol, tylosin, lincomycin, gentamycin, spectinomycin and streptomycin) against M. hyopneumoniae. Methods and Results:  Flow cytometry was able to detect Mycoplasma hyopneumoniae inhibition at 12 h postincubation, whereas the results obtained by the traditional method were only obtained at 48 h, when a visib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
11
0
2
Order By: Relevance
“…The results obtained with this approach were comparable with those obtained by the classical broth dilution method, which is dependent on the observation of a color change or increasing turbidity in the growth medium. However, the FCM approach was faster (12 h) than the broth dilution method (48 h), and furthermore, it was concluded that at 48 h FCM was more sensitive for tylosin and at 72 h for oxytetracycline and streptomycin MIC determination [44]. …”
Section: Application Of Flow Cytometrymentioning
confidence: 99%
“…The results obtained with this approach were comparable with those obtained by the classical broth dilution method, which is dependent on the observation of a color change or increasing turbidity in the growth medium. However, the FCM approach was faster (12 h) than the broth dilution method (48 h), and furthermore, it was concluded that at 48 h FCM was more sensitive for tylosin and at 72 h for oxytetracycline and streptomycin MIC determination [44]. …”
Section: Application Of Flow Cytometrymentioning
confidence: 99%
“…This is a fast and accurate method for counting the viability of the microorganisms compared to the traditional CFU counting method (23). The use of flow cytometry with DNA dyes and membrane-impermeant probes for determining the viability of various Mycoplasma species has been developed recently (44)(45)(46)(47)(48). We have for the first time applied this method to Ureaplasma spp.…”
Section: Discussionmentioning
confidence: 99%
“…The application of FC to research and routine procedures [52,193,194] have shown several advantages in diagnostic and the identification of clinically important species [195][196][197], the assessment of drugs and antibiotics effects on cell viability [32,100,130,149,[198][199][200][201] as well as in cell characterization [202,203] and the study of gene regulation and expression in pathogens [98], among others. Recently, the application of an improved two-colour FC assay combining bioconjugated fluorescent nanoparticles and SYBR Green I allowed the detection of Mycobacterium tuberculosis cells avoiding false positives in clinical diagnosis [204].…”
Section: Pharmaceutical Industry and Medical Applicationsmentioning
confidence: 99%